Ochotnicza straż pożarna jednostką ochrony przeciwpożarowej - Nowicki, Henryk (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
This article presents a legal status of volunteer fire departments and their role in the fire safety system. It pays particular attention to the fact that the activity in the field of fire safety belongs to public task, in this case carried out by social organisations. Taking into account the legal status of the volunteer fire departments acting as associations which often have a character of public benefit organisations, the author postulates a clear statutory indication of the legal nature of the volunteer fire departments as associations with legal personality. Therefore it is important to equip the volunteer fire departments with professional legal and fund management which should be provided by the relevant municipalities.
Keywords: ochotnicza straż pożarna; działania; stan prawny; stowarzyszenia; organizacja pożytku publicznego